Vicia liupanshanensis (Fabaceae), a new plant species from northwestern China - Bo Yang; Jun Yang; Siyu Wei; Hongmei Zhang; Xiaowei Li (PhytoKeys)
A new legume species, Vicia liupanshanensis, discovered in the southern Ningxia Hui Autonomous Region and central Gansu Province of northwestern China, is described and illustrated. The distinguishing characteristics of this herbaceous plant include its semi-sagittate stipules and the presence of 7–9 pairs of leaflets in its leaves. The racemose inflorescence, which is approximately equal in length to the leaf, features rhombic bractlets (5–7 mm long) covered with short, soft hairs. The secund flowers, arranged along one side of the inflorescence, are slightly drooping, approximately 1 cm in length. The corolla displays a shift in colour from pale greenish-creamy-white to yellow-brown, dark yellow, or dark orange. In accordance with the criteria established by the IUCN Red List, the species Vicia liupanshanensis is evaluated as being of Vulnerable status (VU).